Two-Step Laser Ablation for the Synthesis of Au:Pb Core/Shell NPs for a High-Performance Silicon-Based Heterojunction Photodetector - Zeina A. Abdul Hameed; Falah A-H. Mutlak (Iraqi Journal of Physics)
In this work, colloidal gold:lead (Au:Pb) core/shell nanoparticles (NPs) were synthesized in liquid at 532 nm using the laser ablation method.  An investigation of the external magnetic field during the laser ablation process affected the properties of the Au:Pb NP core and shell. The magnetic field enhances the core shell’s crystallinity. The optical band gap energy increased from 2.067 to 2.086 eV in the presence of the magnetic field. It also led to an increase in the concentration and a decrease in the size of nanoparticles, which led to increased absorbance. A magnetic field strength of 250 mT resulted in a higher removal efficiency. The external magnetic field significantly reduced NP agglomeration and aggregation. We created and characterized an Au:Pb/porous silicon (PS) heterojunction photodetector. The magnetic field greatly enhanced its properties. The responsively (Rλ) of the photodetector increased from 0.093 to 0.551 A/W at λ = 650 nm by increasing the magnetic field. On the other hand, the final Au:Pb/PS material had the best photocurrent stability, demonstrating that adding Au:Pb NPs can make PS's opto-electrical properties more stable. In the end, the Au:Pb NPs/PS heterojunction photodetector results showed that the photodetector parameters got much better when a magnetic field was present. By altering the preparation conditions, we can produce high-performance core/shell photovoltaic devices.